Essential preparations - 4 0 16; 5 (Australia : Video Education Australasia, 2006)
Using practical skill demonstrations, role-plays, computer graphics and descriptive narration, this series explains the many skills, competencies and personal attributes needed to gain employment in the hospitality sector. This series is an essential resource for every Australian TAFE College and RTO delivering courses in tourism and hospitality, especially Certificate IV in Hospitality (Food & Beverage Service); and an invaluable resource for VET students studying hospitality units. This episode covers Types of Menus, Basic Equipment and Laying of Tables and Covers.
DVD format.
Keywords: 2 -- 0; 6; Table setting and decoration.;Food service management.;Hospitality industry. -- 20; 20; 2